HAK KEPERDATAAN DAN AKIBAT HUKUM SEBAGAI PEMEGANG HAK GUNA BANGUNAN DALAM HAL BERAKHIRNYA JANGKA WAKTU HAK GUNA BANGUNAN DI SANGATA - Awang Adi AJuniastara (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT AWANG ADI JUNIASTARA. Civil Rights and DueLegalLand Rights Holders in The Event of Expire of Building Rights at Sangatta. Hak Keperataan Dan Akibat Hukum Sebagai Pemegang Hak Guna Bangunan Dalam Hal Berakhirnya Jangka Waktu Hak Guna Bangunan Di Sangatta, Supervisors by Drawan Hasyim, SH, M.Si and Isnawati,SH,MH The rights of land by person suitable with the legal of national land which protection of other parties without the valid right reason in all of form as well as in physic or non physic. Thus also the right of land cannot to deprived and with the unlawfully include by ruler. The main problem which have attention related with building rights of state land namely in the event of expire of Building Right it, what the land rights holder have civil right which have to be state land. Thus also the due legal in the event of expire of building rights on the ex landrighs holders.These research aimed to know the civil rights of land rights holder in the event of expire of building rights and what the due legal in the event of expire of building rights by holders. The result of studied showed that the building rights namely the rights to building and have built on the land which not his own in the certain time, as long as 30 years in meaning that the risk from land rights holder is limited, but the time of own could to be extended during 20 years and updated during 30 years the rights of mutual agreement, during the person or corporation have criteria to obtained the building rights. The building rights have priority rights to take back when the building rights not to extended or uptodate, so the building rights would to delete because end of time it. The land state if the end of time so could be back to state but the building and goods, the holders have right to be own. With thus the end it the right of land, while about the building and goods, fully owned building rights holders.Keywords:      Civil Rights, Land Rights Holders in The Event of Expire of Building Rights